Assessment and management of burn pain at the Komfo Anokye Teaching Hospital: a best practice implementation project. (September 2017) - Bayuo, Jonathan; Munn, Zachary; Campbell, Jared
EXECUTIVE SUMMARY: Background: Pain management is a significant issue in health facilities in Ghana. For burn patients, this is even more challenging as burn pain has varied facets. Despite the existence of pharmacological agents for pain management, complaints of pain still persist. Objectives: The aim of this project was to identify pain management practices in the burns units of Komfo Anokye Teaching Hospital, compare these approaches to best practice, and implement strategies to enhance compliance to standards. Methods: Ten evidence-based audit criteria were developed from evidence summaries. Using the Joanna Briggs Institute Practical Application of Clinical Evidence Software (PACES), a baseline audit was undertaken on a convenience sample of ten patients from the day of admission to the seventh day. Thereafter, the Getting Research into Practice (GRiP) component of PACES was used to identify barriers, strategies, resources and outcomes. After implementation of the strategies, a follow-up audit was undertaken using the same sample size and audit criteria. Results: The baseline results showed poor adherence to best practice. However, following implementation of strategies, including ongoing professional education and provision of assessment tools and protocols, compliance rates improved significantly. Atlhough the success of this project was almost disrupted by an industrial action, collaboration with external bodies enabled the successful completion of the project. Conclusion: Pain management practices in the burns unit improved at the end of the project which reflects the importance of an audit process, education, providing feedback, group efforts and effective collaboration.